Gobernanza y gestión de áreas protegidas - Worboys, Graeme; Lockwood, Michael, 1955-; Kothari, Ashish, 1961-; Feary, Sue; Pulsford, Ian (Universidad El Bosque ; ANU Press, 2019)
Protected area governance and management presents a compendium of original text, case studies and examples from around the world, drawing on the literature, knowledge and experience of people involved in protected areas. The book synthesizes current knowledge and cutting-edge thinking from the various branches of practice and learning relevant to the management and governance of these areas. It is intended to be an investment in the skills and competences of the people responsible for such a task and, consequently, effective governance and management, now and in the future. The global success of the protected area concept lies in its shared vision of protecting long-term natural and cultural heritage, and organizations such as the International Union for Conservation of Nature are a unifying force in this regard. However, protected areas are a socio-political phenomenon and the ways in which nations understand, govern and manage them are always open to disputes and debates. The book aims to illustrate, educate and, above all, challenge readers to think deeply about protected areas, their future and past, as well as their present. The book has been compiled by 169 authors and covers all aspects of the governance and management of protected areas. Provides information to support capacity development training for field officers, managers in charge, and executive level managers. This is the Spanish translation of Protected Area Governance and Management.